Strategies to achieve the African Union's 10-year action plan for fertilizer and soil health: a policy brief - Rasche, F.; Roobroeck, D.; Muzata, B.S.; Vanlauwe, B. (International Institute of Tropical Agriculture, 2024)
This policy brief addresses the challenges and strategies for achieving the African Union’s 10-year action plan for fertilizer and soil health. Key recommendations include enhancing multi-sectoral partnerships, advancing research and development, fostering intentional investment, and promoting inclusive capacity development.